DETERMINATION OF TEACHERS’ PERCEPTIONS OF MUSEUM EDUCATION: A METAPHOR ANALYSIS STUDY - Esra Karabacak, Havva; Gökbulut, Burak; Yeniasir, Mustafa (Revista Inclusiones, 2020)
The objective of this study is to identify the metaphors developed by pre-service teachers as regards museum education which is added as an elective course to the curricula of departments related to teaching in the 2018-2019 academic year after gaining popularity in Turkey recently. Thus, the perceptions and perspectives of prospective teachers on museum education, which will have a much more important position in the future education curricula, are revealed. The study group consisted of 60 pre-service teachers. In the study, the metaphors of the pre-service teachers about museum education were determined with a semi-structured form.